School Health Promotion at the Time of COVID-19: An Exploratory Investigation with School Leaders and Teachers - Francesca Brivio; Laura Fagnani; Simona Pezzoli; Ilenia Fontana; Luca Biffi; Alessandro Domenico Mazzaferro; Veronica Velasco; Andrea Greco (MDPI AG, 2021)
The Coronavirus pandemic has impacted the entire school population's emotions and the disruption of the organization of the school world. In this context it is important to reflect on the role of health promotion at school. The present study aimed at exploring school leaders' and teachers' perspectives and experiences about COVID-19 pandemic and its effects in the school and education system. The first objective was to gather the experience of school leaders regarding the change in school organization, with particular attention to organizational and health promotion aspects. The second was to investigate the perception of health promotion and self-efficacy of teachers in primary, middle and high schools. The research was conducted using qualitative (focus groups for the school leaders) and quantitative methods (questionnaires for the teachers). The findings showed new ways of improving wellbeing at school and implementing health promotion through the sharing of good practice between school leaders. The need for time and space to reflect among school leaders on the educational and didactic aspects of school organization also emerged. Teachers showed a low to medium level of self-efficacy regarding the adoption of strategies in line with health promotion; specificities for each grade and level will be discussed.